210k views
3 votes
Expand: f(x) = (x-2)(x-5)(x-√3)(x+√3)

Expand: f(x) = (x-2)(x-5)(x-√3)(x+√3)-example-1
User Nategoose
by
6.2k points

2 Answers

5 votes

Answer:

x∧4-: 7

x³+: 7

x²+: 21

x-: 30



User Lyrl
by
5.5k points
2 votes
f(x) = (x-2)(x-5)(x-√3)(x+√3)

Let's start by multiplying the first two binomials:

f(x) = x^2 - 7x + 10(x-√3)(x+√3)

Now multiply the second binomials:

f(x) = (x^2 - 7x + 10)(x^2 - 3)

Now multiply the two polynomials:

f(x) = x^4 - 7x^3 + 10x^2 - 3x^2 + 21x - 30

Now combine like terms:

f(x) = x^4 - 7x^3 + 7x^2 + 21x - 30
User Carlos Vergara
by
6.4k points